2016
DOI: 10.1044/2015_lshss-14-0098
|View full text |Cite
|
Sign up to set email alerts
|

Voice Disorder Management Competencies: A Survey of School-Based Speech-Language Pathologists in Nebraska

Abstract: School-based SLPs' competence perceptions with voice disorders are consistent with the minimal levels of competence reported for other underserved or low-incidence populations. Pursuing continuing education in voice disorders is recommended at the same time as access to the population becomes available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Nevertheless, the majority of participants surveyed in that investigation reported low-confidence levels. Different findings were reported in a study of school-based SLPs' selfefficacy perception in treating voice disorders (Teten et al, 2016). Participants reported being (on average) minimally to somewhat competent in treating voice disorders, with SLPs who had attended CE programs in the 5 years prior to the study feeling more competent than those who attended less recent CE programs.…”
Section: Self-efficacy and Clinicalmentioning
confidence: 56%
See 1 more Smart Citation
“…Nevertheless, the majority of participants surveyed in that investigation reported low-confidence levels. Different findings were reported in a study of school-based SLPs' selfefficacy perception in treating voice disorders (Teten et al, 2016). Participants reported being (on average) minimally to somewhat competent in treating voice disorders, with SLPs who had attended CE programs in the 5 years prior to the study feeling more competent than those who attended less recent CE programs.…”
Section: Self-efficacy and Clinicalmentioning
confidence: 56%
“…Incorporating problem-based learning (PBL) into CE programs has been shown to have a positive effect on the professional practice patterns of healthcare providers such as physicians (Davis et al, 1999;Fletcher, 2007;Mansouri & Lockyer, 2007), but few studies have explored whether PBL CE programs alter the clinical practice patterns of speechlanguage pathologists (SLPs). Some studies have found an association between the extent of CE training and SLPs' self-perception of their efficacy in treating dysphagia (Fishbein, Flock, & Benton, 2013;O'Donaghue & Dean-Claytor, 2008) or voice disorders (Teten, DeVeney, & Friehe, 2016), but investigators did not consider whether SLPs altered their treatment practice patterns because of such CE training. In this pilot investigation, we explored whether SLPs' self-perception of efficacy and treatment practice patterns were associated with PBL CE training in treatment of childhood apraxia of speech (CAS) and what aspects of the PBL CE experience SLPs considered most impactful to their learning.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of voice problems in children, only a very small percentage of children seek treatment [2]. Clinicians are not confident in providing treatment for children with voice problems [28]. Although some children may outgrow the voice problems, there is a lack of empirical evidence and data in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Voice evaluation and treatment have been identified as areas in which clinicians and their employers feel they are underprepared. School and medical SLPs in Nebraska indicated that they did not feel prepared to evaluate and treat voice disorders (Teten et al, 2016). The medical SLPs' confidence level (M = 2.41, 1 = minimally prepared and 5 = extremely prepared) was higher than the school SLPs' confidence level (M = 1.94).…”
Section: Overview Of Graduate Student Preparation In Voicementioning
confidence: 91%
“…This study investigated the influence of motor training on perceptual skills in naïve listeners to consider additional methods to effectively train Master's SLP students in the clinical judgment of voice quality. The preparation of Master's SLP students to evaluate and treat voice varies widely (Teten, DeVeney, & Friehe, 2013;Van Mersbergen, Ostrem, & Titze, 2001) and new clinicians did not feel confident in their abilities (Teten, DeVeney, & Friehe, 2016). Research studies on vocal perceptual evaluations looked further into why perceptual ratings were less reliable and what could be done to improve them.…”
Section: List Of Figuresmentioning
confidence: 99%